Utilization of Fermented Salted Marine Trashfish Meal for Replacing Fishmeal in Nemurus Catfish (Hemibagrus nemurus) Diets. Issue 1 (March 2021) - Hasan, B.; Iriani, D.; Sumarto,; Warningsih, T.
Abstract: This research was carried out to determine the substitution values of fermented salted marine trash fish (FSMTF) for dietary conventional fishmeal (CFM) on growth of nemurus catfish. Four isoproteic (34% crude protein) and isocaloric (3.15 kcal DE g −1 ) diets were formulated. One diet was a control diet (C) in which 44% CFM was included and no FSMTF. Other three diets were test diets in which CFM was substituted with FSMTF, 50% (FSMTF-50), 75% (FSMTF-75) and 100% (FSMTF-100). A commercial diet (COM) which composed of 31 % crude protein and 2.90 kcal DE g −1 was also tested as a comparison. Nemurus catfish, 47±3.94 g in weight were distributed into triplicate net cages (2x2x1.5 m), 40 fishes per m 3 water, and fed experimental diets two times daily for two months. Total substitution of fishmeal with FSMTF (FSMTF-100) in the fish diet did not affect fish growth (weight gain, specific growth rate, survival rate), feed efficiency ratio, protein efficiency ratio and protein utilization as compared to control diet. Total substitution of CFM with FSMTF gave better feed efficiency ratio, protein efficiency ratio and protein utilization than commercial diet. FSMTF therefore can completely replace CFM in the diet of nemurus catfish.